INCREASED CUSTOMER SATISFACTION THROUGH PRODUCT QUALITY, PRICE AND BRAND IMAGE (STUDY ON ROWN DIVISION OF SURAKARTA) - Dewanto, Andrew Rudi; Nuryati, Nuryati; YPE, Yosephine Angelina (KELOLA, 2018)
The purpose of this research is to know the influence of product quality, price and Brand Image towards customers satisfaction in Rown Division. The sample of this research as much as 100 respondents. Data analysis tools: test instruments, test the assumptions of classical, linear regression analysis of multiple test, t test, F test, and R2. The results of the regression analysis showed that the quality of the product, the price and the Brand Image of a positive effect towards customer satisfaction. Test results showed that t: product quality and Brand Image of a positive and significant effect against customer satisfaction, while the Price effect is negative and insignificant towards customer satisfaction. F test results showed together – the same variable product quality, price and Brand Image effect significantly to customer satisfaction. Test results the coefficient of Determination (R2) of the Adjusted R Square value obtained as a result of 0.592 which means customer satisfaction in Surakarta Rown Division able to be explained by the variable quality of the product, the price and Brand Image of 59.2%, while the remaining 40.8% is explained by other variables did not enter terobservasi. For example: promotion, distribution and quality of service. Keywords: quality of product, pricing, Brand Image and customer satisfaction.